Determination of parameters for obtaining and conservation of adult bovine rennet - Córdova, Javier S. (2013)
The present research was conducted in order to determine the parameters of production and conservation of adult bovine rennet. Dry abomasum was chunked and proceeded to the extraction of the enzyme with hydrochloric acid 3 mM, pH 2,5. Was activated enzyme solution and filtered to yield the liquid rennet with 1:607,59 force (± 1,58) Soxhlet Units. Liquid rennet was filled in low density polyethylene milky white bottles and stored for one month at 4°C, -7°C and -198°C, to later evaluation. The strength of liquid rennet in storage at 4°C did not yield good results, because loss of the 38,47% of force. Stored liquid rennet to temperature of -7°C, generated a power loss of 30,94%, being the basal strength of 1:419,58 (± 1,47) in U.S. (Units Soxhlet). Storage of liquid rennet to -198°C (liquid nitrogen), was appropriate to preserve with power loss.